Factors influencing nurses’ attitudes towards information technology in nursing practice in Western Australia - Suppiah Dall, Veronica-Ann (Curtin University, 2014)
To understand factors that influence Western Australian nurses’ attitudes towards using information technology in nursing practice, a mixed-methods approach involving quantitative and qualitative approaches was used. A questionnaire was responded to by 134 registered nurses and this was followed by interviews with selected participants. Various barriers that hampered nurses’ embracing computers and information technology were identified.